La conquista de Mesoamérica desde la perspectiva de una teoría mundial - Carmack, Robert M. (Revista de historia., 1993)
The author seeks to apply the theoretical model of the “Word system” to the conquest of Mesoamerica, so as to clarify various obscure aspects of this process.